2009
DOI: 10.1590/s1982-56762009000500003
|View full text |Cite
|
Sign up to set email alerts
|

Influência da luminosidade e da camada de cera epicuticular de superfícies de folhas de soja na infecção de Phakopsora pachyrhizi

Abstract: INTRODUÇÃOA ferrugem asiática da soja, causada pelo fungo basidiomiceto Phakopsora pachyrhizi Syd. & P. Syd foi relatada pela primeira vez no Japão, em 1903 (Henning, 1903, sendo considerada uma importante doença foliar na África, Asia, Austrália e América do Sul, com danos variando entre 10 a 90% (Sinclair e Hartman, 1999;Yorinori et al., 2005;Levy, 2005). Além da soja, o fungo pode infectar mais de 60 espécies em 52 gêneros de leguminosas pertencentes à família Fabaceae (Rytter et al., 1984;Ono et al., 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…() and Furtado et al. () observed a significant reduction in uredospores germination and appressorium formation when leaves were incubated under light in comparison with dark. The absence of light favoured greater intensity of grey mould when the abaxial or adaxial leaf eucalypt was inoculated with a conidial suspension of B. cinerea .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…() and Furtado et al. () observed a significant reduction in uredospores germination and appressorium formation when leaves were incubated under light in comparison with dark. The absence of light favoured greater intensity of grey mould when the abaxial or adaxial leaf eucalypt was inoculated with a conidial suspension of B. cinerea .…”
Section: Discussionmentioning
confidence: 92%
“…Incubation of eucalypt plants inoculated with uredospores of Puccinia psidii in the presence of light also proved unfavourable for germination and infection of this fungus (Ruiz et al 1989). For Phakopsora pachyrhizi on soya bean leaves, Li et al (2010) and Furtado et al (2009) observed a significant reduction in uredospores germination and appressorium formation when leaves were incubated under light in comparison with dark. The absence of light favoured greater intensity of grey mould when the abaxial or adaxial leaf eucalypt was inoculated with a conidial suspension of B. cinerea.…”
Section: Discussionmentioning
confidence: 94%
“…J., Uberlândia, v. 35, n. 2, p. 398-408, Mar./Apr. 2019 microclimate becomes more favorable because it prevents the solar radiation action at the lower third of the plants (FURTADO et al, 2009). Thus, an estimation of genotypes agronomic parameters is necessary when analyzing soybean rust severity.…”
Section: Resultsmentioning
confidence: 99%
“…According to Furtado et al (2009) Thus, the optimal biomass must be studied for each variety of soy, avoiding overgrowth and potential problems brought by diseases.…”
Section: Methodsmentioning
confidence: 99%